Anthropogenic greenhouse gas concentrations and global temperature: a smooth transition analysis - Michail, Nektarios A.; Savva, Christos S.; Koursaros, Demetris; Zachariadis, Theodoros (My University, 2019)
This study examines for the existence of a nonlinear relationship between changes in anthropogenic concentrations of greenhouse gases (forcings) and changes in global temperature, using a smooth transition conditional correlation model. The findings suggest that the correlation between the two is practically zero before a threshold value of anthropogenic concentrations is reached, but rises significantly after this threshold is exceeded. The threshold can be traced back in the mid-1960s, during the years of economic growth in industrialized nations. Thus, the results provide an explanation as to the reason why previous studies had, at times, failed to find a significant relationship.
Keywords: Global temperature; Conditional correlation; Anthropogenic concentrations